A case of acute disseminated encephalomyelitis in a pediatric patient presenting with isolated bilateral optic neuritis [İzole bilateral optik nörit ile prezente olan pediyatrik akut dissemine ensefalomyelit olgusu] - (:unkn) unknown (Duzce University Medical School, 2014)
Acute disseminated encephalomyelitis (ADEM) is an inflammatory disease which is characterized by demyelination of the central nervous system. Optic neuritis is the most common ophthalmic manifestation of the disease. Various neurological symptoms can be seen according to the extent of the disease. Because of the increased risk of multiple sclerosis development; diagnosis, treatment and follow-up of ADEM is essential. Our aim was to present a case of pediatric ADEM, which presented with optic neuritis alone in the light of current literature. © 2012 Düzce Medical Journal.
Keywords: Acute disseminated encephalomyelitis; Childhood; Optic neuritis